Contribution to evaluation of technical seismicity effect on buildings - case study (2006)
The study of seismic loading on buildings and structures caused by technical seismicity has intensified due to increase in loads. Loads are of interest not only for existing structures but they must be checked as partof an entire documentation project for new relevant buildings or for planned building reconstruction.The regions of Ostrava and Karviná were selected for study. The main reasons of our choice are the simultaneous occurrence of different types of technical seismicity: Mining induced seismicity, trafficvibrations, industrial activity effects, etc., and the existence of suitable structures for experimental measurement in this area. Individual buildings require different approaches for evaluation of their seismicload according to actual Czech technical standards.The most suitable set for initial studies will be a group of selected buildings and structures meeting the most rigorous criteria for judging the seismic loading. Reliable measurements from analyzed buildingsand structures are available for experimental work in the area. The number of places for experimental measurements will decrease after comparation with information of actual seismic loads caused by certaintype of technical seismicity in this area. The result of this evaluation will be the so-called maps of clashes of opinions, which should help to choose the measurement area and suitable structures.